DOM dynamics in open waters of the Mediterranean Sea: New insights from optical properties. (February 2019) - Galletti, Y.; Gonnelli, M.; Retelletti Brogi, S.; Vestri, S.; Santinelli, C.
Abstract: In the Mediterranean Sea (Med Sea), Dissolved Organic Matter (DOM) dynamics shows some peculiarities that can be investigated by using its optical properties. Despite being a marginal sea, the Med Sea behaves as a miniature ocean for DOM concentrations and distribution. Its surface waters are "greener" than it would normally result from their generally low phytoplankton content and in the deep waters DOC is ~1000 years older and more degraded than in the Atlantic Ocean. These observations suggest a greater contribution of allocthonous substances to the DOM pool in this basin. With this work we aim at presenting new data on optical properties of chromophoric DOM (CDOM) and fluorescent DOM (FDOM) in open sea waters of the Med Sea, in order to investigate the main drivers of CDOM and FDOM dynamics in both surface and deep waters and to get insights into their origin. Our data confirm the occurrence of DOM with a different composition with respect to the oceans and suggest some differences with respect to other marginal basins, opening intriguing questions about the source and cycle of allocthonous molecules in the open sea waters of the Med Sea. CDOM absorption in the western Med Sea and Ionian Sea is generally lower than that observed in the other marginal seas, but higher than in the oceans. The parallel factor analysis unveiled the presence of one PAH-like and one terrestrial humic-like component that were found in the other marginal basins but that were not found in the open oceans. In contrast to the oceans and most of the marginal seas, only one protein-like component was found. Net production of humic-like FDOM as function of mineralization was not observed in the intermediate and deep waters of the Med Sea, supporting that in this basin CDOM/FDOM dynamics is different than in the oceans. In the surface layer, photobleaching plays a relevant role in the removal of humic-like fluorescence, and the release of both protein-like and humic-like substances occurs in proximity of the deep chlorophyll maximum. Highlights: Humic acids are a major component of DOM pool in the Med Sea. No production of humic-like FDOM as function of mineralization rates. a254 can be a good proxy for DOC in the Med Sea. Protein-like and humic-like substances are released in the surface layer. External sources plays a crucial role in DOM dynamics in the Med Sea.